2017
DOI: 10.13189/sa.2017.050504
|View full text |Cite
|
Sign up to set email alerts
|

Parent-child Relationship and Filial Piety Affect Parental Health and Well-being

Abstract: The purpose of this study is to examine the effects of parent-child relationship, filial piety and adult children's concept of family on the health and well-being of their parents. Data were obtained from the Panel Study of Family Dynamics in Taiwan, 2005Taiwan, -2011. The sample comprised parents with repeated measures and one wave data from their adult children (208 persons with 1,336 observations). The parent-child relationship predicted self-rated health for both fathers and mothers and predicted the life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In a study of 432 poor single-mother families in Hong Kong, Leung and Shek [ 36 ] found that higher filial piety was associated with better adolescent development. Filial responsibility was also positively linked to parent–child cohesion [ 17 ], which may reduce maternal distress [ 37 ]. From this view, filial responsibility may serve as a buffer that smooths the association of maternal distress with adolescent mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 432 poor single-mother families in Hong Kong, Leung and Shek [ 36 ] found that higher filial piety was associated with better adolescent development. Filial responsibility was also positively linked to parent–child cohesion [ 17 ], which may reduce maternal distress [ 37 ]. From this view, filial responsibility may serve as a buffer that smooths the association of maternal distress with adolescent mental health problems.…”
Section: Introductionmentioning
confidence: 99%